Pengembangan Pembelajaran Pendidikan Agama Islam yang Integratif-Inklusif dalam Meningkatkan Keberagaman Karakter Peserta Didik - Vivi Alvina Damayanti; Muhammad Misbah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The rapid transformation of 21st-century education requires Islamic Religious Education (PAI) to move beyond knowledge transmission by accommodating learner diversity while strengthening character development. This study aims to analyze the concept of integrative-inclusive PAI learning and examine its contribution to strengthening students' character in diverse educational settings. This research employed a qualitative approach using the library research method. Data were collected through document analysis of books, scholarly journals, scientific articles, and other relevant academic sources, and subsequently analyzed using content analysis to identify, classify, and interpret information in accordance with the research objectives. The findings reveal that integrative-inclusive PAI learning is grounded in strong pedagogical and Islamic normative principles, emphasizing justice, equality, respect for diversity, student-centered learning, and flexibility in instructional practices. Its implementation can be realized through differentiated learning, collaborative learning, Project-Based Learning, contextual learning, the integration of digital technology, and reflective learning activities. These approaches contribute significantly to fostering religious character, tolerance, religious moderation, empathy, social responsibility, collaboration, critical thinking, and communication skills among students. Although its implementation continues to face challenges, including limited teacher competence, inadequate educational facilities, and the predominance of cognitively oriented instructional paradigms, substantial opportunities remain through the implementation of the Merdeka Curriculum, continuous professional development for teachers, educational technology integration, and collaborative partnerships among schools, families, communities, and the government. The findings underscore the importance of developing integrative-inclusive PAI learning as a relevant educational paradigm for cultivating religious, humanistic, moderate, adaptive, and well-rounded students in the context of 21st-century education. Keywords: Islamic Religious Education, Integrative-Inclusive Learning, Character Building